SWI/SNF-dependent long-range remodeling of yeast HIS3 chromatin - Kim, Yeonjung (National Academy of Sciences, 2002)
Current models for the role of the SWI/SNF chromatin remodeling complex in gene regulation are focused on promoters, where the most obvious changes in chromatin structure occur. Here we present evidence that the SWI/SNF complex is involved in the remodeling of the chromatin structure of an entire gene in vivo. We compared the native chromatin structures of a small yeast plasmid containing the HIS3 gene purified from uninduced and induced cells. Relative to uninduced chromatin, induced chromatin displayed a large reduction in negative supercoiling, a large reduction in sedimentation rate, and increased accessibility to restriction enzymes with sites located both near and far from the HIS3 promoter. These observations indicate that the entire plasmid was remodeled as a result of induction. Loss of supercoiling required the presence of the SWI/SNF remodeling complex and the activator Gcn4p in vivo. The TATA boxes were not required, suggesting that remodeling was not the result of transcription. The induction-dependent loss of negative supercoiling was not apparent in cells, indicating that the supercoils were lost preferentially from induced chromatin during purification. Thus, induced HIS3 chromatin has a highly labile structure that is revealed as a result of purification. It is concluded that induction of HIS3 creates a domain of labile chromatin structure that extends far beyond the promoter to include the entire gene. We propose that the SWI/SNF complex is recruited to the HIS3 promoter by Gcn4p and then directs remodeling of a chromatin domain, with important implications for transcription.